Baits for Sampling Wireworms in Southern Florida's Agricultural Fields - José Alvarez; Ronald Cherry (EDIS)
SC078, a 3-page fact sheet by José Alvarez and Ronald Cherry, is a new addition to the UF Agronomy Department's electronic Sugarcane Handbook. It provides the basic data necessary for growers in the Everglades Agricultural Area to use rolled oats baits as a sampling tool to determine whether it is necessary to apply pesticides for wireworm control before planting. Published by the UF Agronomy Department, August 2006.